2022
DOI: 10.3390/ijerph192416720
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seroconversion and Pregnancy Outcomes in a Population of Pregnant Women Recruited in Milan, Italy, between April 2020 and October 2020

Abstract: The possible link between SARS-CoV-2 infection and adverse pregnancy outcomes has so far demonstrated heterogeneous results in terms of maternal, fetal, and neonatal complications. We aim to investigate the correlation between SARS-CoV-2 seroconversion and/or neutralization titer and pregnancy outcomes. We analyzed a population of 528 pregnant women followed up from the first trimester of gestation until delivery. For each woman, we collected a first blood sample between 11 and 13 weeks of gestation and a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In a retrospective study evaluating 882 positive pregnant women with rRT-PCR SARS-CoV2, including 85 women diagnosed in the first trimester, it was reported that gestational age at the time of infection was the best predictor for gestational age at delivery [27]. To the best of our knowledge, there is only one study that has been conducted to assess SARS-CoV2 serology during both the first and third trimesters while examining the potential association between the presence of antibodies and pregnancy outcomes [28]. In this study, which involved 528 singleton pregnant women, the authors carried out serological assessments during the initial 11-13-week screening visit and again upon the admission for delivery.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…In a retrospective study evaluating 882 positive pregnant women with rRT-PCR SARS-CoV2, including 85 women diagnosed in the first trimester, it was reported that gestational age at the time of infection was the best predictor for gestational age at delivery [27]. To the best of our knowledge, there is only one study that has been conducted to assess SARS-CoV2 serology during both the first and third trimesters while examining the potential association between the presence of antibodies and pregnancy outcomes [28]. In this study, which involved 528 singleton pregnant women, the authors carried out serological assessments during the initial 11-13-week screening visit and again upon the admission for delivery.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The study included 231 pregnant women who were recruited at the Fetal Medicine Unit of the Policlinico Hospital in Milan (Italy), between April and September 2020. The study is a nested case-control study embedded in a larger investigation that has been previously described [56].…”
Section: Subject Enrollment and Blood Sample Collectionmentioning
confidence: 99%
“…Data on pregnancy outcomes and neonatal parameters were collected from the hospital medical records if delivery occurred at our hospital, or by telephone interview otherwise. The diagnosis of adverse pregnancy outcomes (i.e., pre-eclampsia, gestational diabetes mellitus, abnormal growth, and delivery < 34 weeks) was made according to guidelines and as reported in [56].…”
Section: Subject Enrollment and Blood Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations